Verificação probabilística de modelos para modelagem e análise de interações de toxinas com sistemas de transporte transmembrânico de íons = Probabilistic Model Checking for modeling and analysis of toxins interactions with transmembrane ionic transport systems - Fernando Augusto Fernandes Braz (2013)
Probabilistic Model Checking (PMC) is a formal verification technique to model and analyze stochastic systems. It can be applied directly to biological systems which present stochastic behavior, including transmembrane ionic transport systems. These systems are responsible for exchanging ions across the cell membrane and participate in several biological processes, such as heart muscle contraction. In this work we have modeled and analyzed four different PMC models of the sodium-potassium-pump, a transport system, and its interactions with a toxin called palytoxin (PTX). This toxin completely disrupts the behavior of the pump. Our models have suggested different results, such as that high concentrations of cell energy (ATP) and sodium inhibit PTX action, while potassium enhances it. This type of analysis can provide a better understanding of cell transport systems behavior, being complementary to approaches such as simulations, and can lead to the discovery and development of drugs.